2004
DOI: 10.1074/jbc.m312160200
|View full text |Cite
|
Sign up to set email alerts
|

The Focal Adhesion Protein Vinexin α Regulates the Phosphorylation and Activity of Estrogen Receptor α

Abstract: Steroid receptors are transcription factors that regulate hormone-responsive genes and whose activity is controlled by their interaction with numerous other proteins. Observations reported here reveal that estrogen receptors ␣ and ␤ (ER␣ and ER␤), androgen receptor, and glucocorticoid receptor bind in vitro to vinexin ␣, a multiple SH3 motif-containing protein associated with the cytoskeleton. The SH3 domains are not involved in this interaction. Furthermore, we demonstrate that vinexin ␣ stimulates the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Indeed, the progesterone receptor interacts with cCbl-associated protein/ponsin through a proline-rich motif in its N-terminal domain (42). The ER has also been recently reported to interact with the ␣ isoform of vinexin through its N-terminal domain (43). Based on these observations, it appears that this family of proteins, which can be present not only in the cytoplasm, but also in the nucleus, would be novel regulators of nuclear receptors.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the progesterone receptor interacts with cCbl-associated protein/ponsin through a proline-rich motif in its N-terminal domain (42). The ER has also been recently reported to interact with the ␣ isoform of vinexin through its N-terminal domain (43). Based on these observations, it appears that this family of proteins, which can be present not only in the cytoplasm, but also in the nucleus, would be novel regulators of nuclear receptors.…”
Section: Discussionmentioning
confidence: 98%
“…Under the conditions, immunoreactivity of anti-phospho-Vin was detected at focal adhesions where GFP-vinexinb accumulated (Figure 3Bd-f). Phosphorylation signal in the nucleus may be related to vinexin-dependent gene-expression control although the possibility of nonspecific signals is not ruled out (Tujague et al, 2004;Bour et al, 2005). As is the case of T24 cells, GFP-vinexinb-SA accumulated at focal adhesions with little phosphorylation signal (Figure 3Bg-k).…”
Section: Intracellular Localization Of Vinexin In Migrating and Spreamentioning
confidence: 97%
“…Moreover, vinexin ␤ regulates the EGF-induced activation of JNK and the anchoragedependent activation of ERK2 induced by EGF (20,21). Furthermore, it was reported that vinexin interacted with scaffold attachment factor B2 or estrogen receptor, both of which are implicated in the response to steroid hormone (22,23). These observations suggested that vinexin is involved not only in the regulation of cell adhesion/cytoskeletal organization, but also in the regulation of signal transduction.…”
mentioning
confidence: 88%
“…Thus, one possibility is that vinexin links the active form of ERK to its substrates as a scaffold protein. We and others reported that vinexin bound to Sos (20) and estrogen receptor (23), both of which are phosphorylated and regulated by ERK (24,46,47), through the third SH3 domain and the N-terminal half of vinexin ␣, respectively. Vinexin bound to the active form of ERK through the linker region between the second and third SH3 domains.…”
Section: Discussionmentioning
confidence: 99%